Nanoparticulate drug-delivery systems: lymphatic uptake and its gastrointestinal applications - Saikat Ghosh and Tanushree Roy (Journal of Applied Pharmaceutical Science, 2014)
One of the important challenges of modern drug therapy is the optimization of the pharmacological action of a drug along with the reduction of its toxic side effects in vivo. One response is the use of drug carriers that can provide site specific or targeted drug delivery combined with optimal drug release profiles. Nanoparticulate systems (NPS) as a drug delivery system is an emerging field in medical sciences since they are believed to target the delivery of the drug in cells reduce dose and thus reduce side effects and dose related toxicities.The gastrointestinal tract (GIT) uptake of nanoparticulate systems is nowadays well accepted phenomenon. Uptake of Nanoparticulates from the gut can provide an additional drug administration route with its own pharmacokinetic parameters and specific drug-carrying ability. The drug is transported into the GIT by carriers whose physico-chemical characteristics must be taken into account, although the physico-chemical and pharmacological characteristics of the drug remain intact. In this article we concentrate particularly on the translocation of NPS via the lymphatic system, and their use.
Keywords: Nanoparticulate systems (NPS),lymphatic system,gastrointestinal tract (GIT) uptake,target,carriers.